Ir. Ts. Dr. Juliawati produces microcapsules composed of honey and linseed oil to enhance metal corrosion resistance - Nur Hartini, Mohd Hatta (UMPSA, 2023)
PEKAN, 20 September 2023 - The cost of repairing or maintaining automotive components, oil and gas pipelines, and the like is not cheap and requires suitable and effective methods to protect metals and materials from corrosion.